Non-HTLV-1-associated primary gastric T-cell lymphoma with cutaneous metastasis and pneumoperitoneum - Meregildo-Rodriguez, Edinson Dante (2022)
Background: Primary gastric lymphomas account for less than 5% of non-Hodgkin lymphomas (NHL). The vast majority of primary gastric lymphomas are high-grade B-cell lymphomas. Primary gastric T-cell lymphomas are very rare and are usually associated with HTLV-1 infection in endemic regions. Material and methods. We describe the case of a middle-aged female patient who presented with pneumoperitoneum due to a perforated gastric ulcer, wasting syndrome, and skin and oral lesions. Results. Histopathology and immunohistochemistry confirmed primary gastric T-cell lymphoma with skin involvement. The serology for HTLV-1, Epstein-Barr virus and HIV were negative. Conclusion. The aim of this report is to present this extremely rare presentation of primary gastric lymphoma.